Development of a drill-based shooting training methodology with experts' verification for footballers aged 13-17 years - Rizki Ade Syukra; Ridho Bahtra; Syahrial Bakhtiar; Alex Aldha Yudi (Indonesian Institute For Counseling, Education and Therapy, 2026)
Shooting accuracy is a crucial determinant of scoring success in soccer. However, many youth football development programs continue to rely on repetitive training methods that may reduce player engagement and limit technical skill development. This study aimed to develop and evaluate a drilling-based shooting training model for junior soccer players in Football Schools (Sekolah Sepak Bola [SSB]) in West Sumatra, Indonesia. This research employed a research and development (R&D) approach using an adapted six-stage Borg and Gall framework, including needs analysis, product design, expert validation, revision, field testing, and effectiveness evaluation. The model was validated by experts in football coaching, research methodology, and language. Small-scale and large-scale field trials involved 12 and 25 players, respectively, with support from three coaches. Effectiveness was assessed using a one-group pretest–posttest design involving 20 players aged 13–17 years. Shooting performance was measured using the Shoot at Goal test and analyzed with a paired-samples t-test. Expert validation demonstrated high feasibility, with an average validity score of 88.96%. Practicality scores ranged from 87.50% to 100.00% across field trials, indicating that the model was highly practical and applicable. Players’ shooting performance improved significantly, with mean scores increasing from 8.25 (SD = 2.43) at pretest to 14.80 (SD = 2.97) at posttest. Statistical analysis revealed a significant difference, t(19) = 12.71, p < .001, accompanied by a very large effect size (d = 2.84). The drilling-based shooting training model is valid, practical, and effective for improving shooting performance among junior soccer players. The model offers a structured and replicable approach to developing fundamental shooting skills in youth soccer training.